Question and Answers Forum

All Questions      Topic List

Coordinate Geometry Questions

Previous in All Question      Next in All Question      

Previous in Coordinate Geometry      Next in Coordinate Geometry      

Question Number 142447 by ajfour last updated on 31/May/21

Commented by ajfour last updated on 31/May/21

Find ellipse perimeter.

Findellipseperimeter.

Answered by Dwaipayan Shikari last updated on 31/May/21

(x^2 /a^2 )+(y^2 /b^2 )=1  ⇒y′=−((b^2 x)/(a^2 y))=−((bx)/(a(√(a^2 −x^2 ))))  Perimetre =2∫_(−a) ^a (√(1+(y′)^2 )) dx  =4∫_0 ^a (√(1+((b^2 x)/(a^2 (a^2 −x^2 ))))) dx    x=ua  =4∫_0 ^1 (1/a)(√((a^4 (1−u^2 )+a^2 b^2 u^2 )/(1−u^2 ))) du      cosθ=u  =4∫_0 ^(π/2) (√(a^2 sin^2 θ+b^2 cos^2 θ)) dθ  =4a∫_0 ^(π/2) (√(1−(1−(b^2 /a^2 ))cos^2 θ)) dθ  =4a∫_0 ^(π/2) (√(1−e^2 cos^2 θ)) dθ=4a∫_0 ^(π/2) (√(1−e^2 sin^2 θ)) dθ  =4aE((π/2)∣e)  Or 4a∫_0 ^(π/2) (√(1−e^2 sin^2 θ)) dθ=4aΣ_(n=0) ^∞ (((−(1/2))_n )/(n!))∫_0 ^(π/2) e^(2n) sin^(2n) θ dθ  =2aΣ_(n=0) ^∞ (((−(1/2))_n e^(2n) )/(n!)).((Γ(n+(1/2))Γ((1/2)))/(Γ(n+1)))  =2πaΣ_(n=0) ^∞ (((−(1/2))_n ((1/2))_n )/(n!(1)_n ))e^(2n) =2πa _2 F_1 (−(1/2),(1/2);1;e^2 )

x2a2+y2b2=1y=b2xa2y=bxaa2x2Perimetre=2aa1+(y)2dx=40a1+b2xa2(a2x2)dxx=ua=4011aa4(1u2)+a2b2u21u2ducosθ=u=40π2a2sin2θ+b2cos2θdθ=4a0π21(1b2a2)cos2θdθ=4a0π21e2cos2θdθ=4a0π21e2sin2θdθ=4aE(π2e)Or4a0π21e2sin2θdθ=4an=0(12)nn!0π2e2nsin2nθdθ=2an=0(12)ne2nn!.Γ(n+12)Γ(12)Γ(n+1)=2πan=0(12)n(12)nn!(1)ne2n=2πa2F1(12,12;1;e2)

Commented by Dwaipayan Shikari last updated on 31/May/21

Approximation  4a(∫_0 ^(π/2) 1−(1/2)e^2 sin^2 θ+O(e^4 ))≈4a((π/2)−((e^2 π)/8))=2πa(1−(e^2 /4))

Approximation4a(0π2112e2sin2θ+O(e4))4a(π2e2π8)=2πa(1e24)

Answered by ajfour last updated on 01/Jun/21

let A be origin.  (((x−a)^2 )/a^2 )+(y^2 /b^2 )=1  (((x−a))/a^2 )+((y((dy/dx)))/b^2 )=0  (dy/dx)=((b^2 (a−x))/(a^2 y))  dl=dx×(√(1+((b^2 (a−x)^2 )/(a^4 {1−(((x−a)^2 )/a^2 )}))))    dl=dx(√(1+((b^2 (a−x)^2 )/(a^2 {a^2 −(a−x)^2 }))))     =dx(√(1+((b^2 /a^2 )/({(1/((1−(x/a))^2 ))−1}))))  let   1−(x/a)=(1/t)  , (b/a)=m  ⇒   −(dx/a)=−(dt/t^2 )  ⇒    dx=((adt)/t^2 )  dl=((adt)/t^2 )(√(1+(m^2 /(t^2 −1))))  let  (m/( (√(t^2 −1))))=tan θ  ⇒   t^2 −1=m^2 cot^2 θ       tdt=−m^2 cot θcosec^2 θdθ  dl=−((am^2 dθ)/(sin^3 θ(1+m^2 cot^2 θ)^(3/2) ))  dl=−((am^2 dθ)/((sin^2 θ+m^2 cos^2 θ)^(3/2) ))  let  sin^2 θ+m^2 cos^2 θ=z^2          (1−m^2 )sin^2 θ=z^2 −m^2   or   (1−m^2 )cos^2 θ=1−z^2   ⇒ (1−m^2 )sin θcos θdθ=zdz       dθ=((zdz)/( (√(z^2 −m^2 ))(√(1−z^2 ))))  dl=−((am^2 dz)/(z^2 (√(z^2 −m^2 ))(√(1−z^2 ))))  let   z=(√m)s ⇒  dz=(√m)ds  dl=((−amds)/(s^2 (√(s^2 −m))(√(1−ms^2 ))))  and if   (1/s)=v  dl=((amv^2 dv)/( (√(1−mv^2 ))(√(v^2 −m))))  dl=((amv^2 dv)/({(1+m^2 )v^2 −m(1+v^4 )}^(1/2) ))  2dl=((a(√m)d(v^2 ))/({(m+(1/m))−(v^2 +(1/v^2 ))}^(1/2) ))  say  v^2 =X , m+(1/m)=h^2   2dl=((a(√m)dX)/( (√(h^2 −(X+(1/X))))))  ....  ........

letAbeorigin.(xa)2a2+y2b2=1(xa)a2+y(dydx)b2=0dydx=b2(ax)a2ydl=dx×1+b2(ax)2a4{1(xa)2a2}dl=dx1+b2(ax)2a2{a2(ax)2}=dx1+b2/a2{1(1xa)21}let1xa=1t,ba=mdxa=dtt2dx=adtt2dl=adtt21+m2t21letmt21=tanθt21=m2cot2θtdt=m2cotθcosec2θdθdl=am2dθsin3θ(1+m2cot2θ)3/2dl=am2dθ(sin2θ+m2cos2θ)3/2letsin2θ+m2cos2θ=z2(1m2)sin2θ=z2m2or(1m2)cos2θ=1z2(1m2)sinθcosθdθ=zdzdθ=zdzz2m21z2dl=am2dzz2z2m21z2letz=msdz=mdsdl=amdss2s2m1ms2andif1s=vdl=amv2dv1mv2v2mdl=amv2dv{(1+m2)v2m(1+v4)}1/22dl=amd(v2){(m+1m)(v2+1v2)}1/2sayv2=X,m+1m=h22dl=amdXh2(X+1X)............

Terms of Service

Privacy Policy

Contact: info@tinkutara.com